SOLAR CYCLES – TO UPDATING BASIC PARAMETERS - Ryabov, M. I. (Одеські астрономічні публікації, 2014)
Examining daily and monthly averages of solar activity index of the northern and southern hemispheres on the total area of spots-Sp (12-24 cycles, 1874-2014), the Wolf numbers-W (22-24 cycles, 1992-2014).  Application of band pass filtering based on Wavelet analysis shows that «Northern» and «Southern» cycles have their own start time, rise phase, the phases of decline, maximum and minimum. The formation of each cycle on all indices of activity is determined as a result of the combined effect of the long-period and shortperiodic processes.